Аналіз уразливостей та загроз у системах управління кіберфізичними об’єктами на прикладі розумної електромережі - Чебурахін, М. І.; Балагура, Д. С. (ХНУРЕ, 2023)
The work examines and analyzes threats and methods of penetration into control systems of cyber-physical objects using the example of a smart power grid, as well as methods for preventing them. Not a single industry in our time can do without methods for protecting confidentiality, integrity and availability, and the smart power grid is no exception, for which information protection is vital, because without information protection, the owner of the power grid can suffer large losses, both financially and and reputational.
Keywords: управління кіберфізичними об’єктами; розумна електромережа